Implementasi E-Commerce dan QRIS Dalam Peningkatan Pendapatan Pada UMKM Cemilan Sultan di Kota Parepare - Damis, Sariana; Nuryadin, Rusmin; Masnawati, Masnawati; Intan, Nur (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The development of e-commerce as part of digital transformation has changed marketing and business transaction patterns, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the implementation of e-commerce and the Quick Response Code Indonesian Standard (QRIS) payment system in increasing revenue for the Sultan Snacks MSME in Parepare City. This study used a qualitative approach with a case study method. Data collection techniques included in-depth interviews, observation, and documentation with business owners and related parties. The data obtained were analyzed using descriptive qualitative analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of e-commerce at the Sultan Snacks MSME is carried out through the use of digital platforms and social media as a means of product promotion and sales, which can expand market reach and increase the number of orders. Furthermore, the implementation of the QRIS payment system provides convenience and speed in the transaction process and helps business owners maintain more orderly financial records.